Effect of varying percentages of Co3O4 Nanoparticles on the Behavior of (ORR/OER) BifunctionalCo3O4/α-MnO2 Electrocatalyst - Zahoor, Awan; Ahmed, Ghadia; Amir, Muhammad; Butt, Faaz; Naqvi, Asad A. (TECCIENCIA, 2023)
Among all types of batteries, Lithium Air Batteries (LAB) are considered to be the most effective due to their highest energy density of around 11,140 Wh/kg but there are some major issues that are being faced by LAB such as large overpotential, poor cycle life, low current density, and decreased energy efficiency. The solution to these issues is primarily dependent on the proper selection of an electrocatalyst. A new approach for using a bi-functional electrocatalyst produced excellent results. Here, Co3O4/α-MnO2 composite has been considered as a bifunctional catalyst because cobalt oxide performed well in the Oxygen Evolution Reaction (OER) process while manganese oxide performed well in the Oxygen Reduction Reaction (ORR) process. A simple two-step hydrothermal process is used in this work to synthesize Co3O4/α-MnO2. This work focuses on the behavior of the composite electrocatalyst when varying percentages of Cobalt oxide (5%, 10%, 15%, and 20%) are deposited on the alpha-Manganese Oxide nanorods. The primary characteristics of each sample with different percentages of Cobalt Oxide are examined, and the performance of each sample is compared to one another. Several testing techniques like Cyclic Voltammetry (CV), Linear Sweep Voltammetry (LSV), X- Ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) are performed on the samples. The combination of cobalt oxide and manganese oxide showed a synergistic effect and work as a bifunctional electrocatalyst. As the percentage of Co3O4 deposited on the α-MnO2 nanorod increased, it behaves more like an OER electrocatalyst leading to a decrease in charging potential. This work will help in finding an optimum amount of Co3O4 that should be deposited on α-MnO2 nanorods to get an efficient (ORR/OER) bifunctional electrocatalyst.